##### Ad

related to: K

... 6/(

**k**+1) - 1/(**k**) = 1 ← note:**k**≠ 0 or -1 or 6(**k**) - (**k**+1) = (**k**+1)(**k**) or 6**k**-**k**- 1 =**k**² +**k**or 0 =**k**² +**k**- 6**k**+**k**...4*3 ) ] / 2**k**= [ 4 ± 2√3 ) ] / 2**k**= 2 ± √3**k**= { 2 - √3, 2 + √3 }**k**~ { 0.2679, 3.7321 }3 Answers · Science & Mathematics · 11/09/2010

**k**= (**k**+15)/3*(**k**-1) ==> multiply both sides by 3(**k**-1) to get rid of fractions 3k(**k**-1) =**k**+15 ==> expand the LHS 3k^2-3k =**k**+15 ==> move everything to the LHS 3k^2-4k-15=0 actually this does...3 Answers · Science & Mathematics · 21/07/2007

2

**k**x² - 12x + (**k**+7) = 0 Solve for**k**b² - 4ac = 0 (b = -12, a = 2**k**and c =**k**...8 ..........-**k**² - 7**k**+ 18 = 0 ..........**k**² + 7**k**- 18 = 0 ........ (**k**- 2) (**k**+ 9) = 0 ......**k**- 2 = 0..........................**k**+ 9 = 0**k**- 2 + 2 = 0 + 2...4 Answers · Science & Mathematics · 12/09/2010

Sources of Vitamin

**K**Vitamin**K**is found chiefly in leafy green ...of vitamin**K**.[7]. Some vegetable oils, notably soybean, contain vitamin**K**, but at levels that would require relatively large caloric consumption to meet the...9 Answers · Food & Drink · 07/03/2009

If

**k**-2 divides 2**k**,**k**-2 ≠ 0, then there is an integer i such that 2**k**= (**k**-2)i Solving for**k**gives... of i less than or equal to 1 that produce**k**≥ 3. Therefore the only ...1 Answers · Science & Mathematics · 20/03/2009

∫(x = 0 to 1) x^

**k**ln x dx = ∫(∞ to 0) (e^w)^**k*** w * (e^w...;==> x = e^w = -∫(w = 0 to ∞) we^((**k**+1)w) dw = -∫(w = 0 to ∞) we^((**k**+1)w) dw...1)t))] = (-1/(**k**+1)^2) * [1 + lim(t→∞) -e^((**k**+1)t)] = (-1/(**k**+1)^2) * (1 + 0), since**k**+1...3 Answers · Science & Mathematics · 10/06/2015

(2

**k**+1) * (2k) * (2k-1) * ... * (**k**+2) * (**k**+1) / 2 = (2k+1) ***k*** [(2k-1) * ... * (**k**+2) * (**k**+1)] In...ellipsis notation from becoming ambiguous. (Otherwise the**k**factor is out of sequence and makes that notation unclear.)1 Answers · Science & Mathematics · 18/07/2011

**K**-9/27 =7/9 Step 1, Multiply 27 to the whole entire problem. 27(**K**-9/27 =7/9) 27K - 9 = 21 Step 2, Add 9 and Divide...2 Answers · Science & Mathematics · 05/05/2012

C=

**K**(Rr/R-r) Divide both sides by**K**: C...r): (R-r)(C/**K**) = Rr Distribute C/**K**: CR/**K**-Cr/**K**= Rr Subtract Rr...4 Answers · Education & Reference · 05/10/2009

**k*** 3^**k**= 1,000,000,000 Start by taking the natural logarithm of both sides of the equation to remove that variable from the exponent:*** ln(3^**k**)(**k**) = ln(1,000,000,000) Now the exponent of a factor here can be ...1 Answers · Science & Mathematics · 21/09/2008

##### Ad

related to: K